2022
DOI: 10.3390/ijms23041953
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channel Partnerships: Odd and Not-So-Odd Couples Controlling Neuronal Ion Channel Function

Abstract: The concerted function of the large number of ion channels expressed in excitable cells, including brain neurons, shapes diverse signaling events by controlling the electrical properties of membranes. It has long been recognized that specific groups of ion channels are functionally coupled in mediating ionic fluxes that impact membrane potential, and that these changes in membrane potential impact ion channel gating. Recent studies have identified distinct sets of ion channels that can also physically and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 117 publications
0
9
0
Order By: Relevance
“…Notably, KvS subunits also modify the pharmacological response of Kv2/KvS heteromers to another pore blocker, 4-aminopyridine (Stas et al, 2015). Another key function of Kv2 channels is to organize ER-PM junctions on neuronal somata and proximal dendrites (Johnson et al, 2019; Vierra and Trimmer, 2022). This structural role is mediated by phosphorylation-dependent binding of the Kv2.1 PRC domain to ER-localized VAP proteins (Johnson et al, 2018; Kirmiz et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, KvS subunits also modify the pharmacological response of Kv2/KvS heteromers to another pore blocker, 4-aminopyridine (Stas et al, 2015). Another key function of Kv2 channels is to organize ER-PM junctions on neuronal somata and proximal dendrites (Johnson et al, 2019; Vierra and Trimmer, 2022). This structural role is mediated by phosphorylation-dependent binding of the Kv2.1 PRC domain to ER-localized VAP proteins (Johnson et al, 2018; Kirmiz et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Pampaloni et al (2018) showed the π electron clouds of sp 2 carbon networks single layer graphene (SLG) interferes with ion bulk diffusion by adsorbing the ions to tip the ionic driving force to change cellular excitability; using a minimal in-silico model it describes how SLGs increase the intrinsic firing of neurons by modulating ion conduction at the graphene-neuron interface; hypothesizing from the same we assume that the spike-adapting excitatory responses by ssw-CNT could be due to possible modulation of Na + conductance as observed from the distinct features in the evoked responses of the treated neurons (Figure 4 and 5). Additionally, reduced intracellular Ca following ssw-CNT incubation (Figure . 3) can also in part account for the enhanced activity of neurons by ssw-CNTs through the reduction of Ca-dependent K ion channel activity that normally functions to reduce neuronal firing (Vierra and Trimmer, 2022). Thus, molecular dynamics simulations of the interactions of the triad of nanomaterial, membrane ion channels and specific ions (Na + , K + , Ca 2+ , Cl -) might give us clues about a possible mechanism of altered ion channel kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that KChIP molecules can act as the calcium sensor for Kv4 channels (Anderson et al, 2010a(Anderson et al, , 2010b, with 4 KChIP subunits present in an assembled channel (An et al, 2000;Vierra and Trimmer, 2022) and EF hands 3 and 4 available to bind calcium. Yet the exact role for KChIP3 in Cav3dependent modulation of Kv4 channels has not been determined.…”
Section: Cav31 and Kchip3 Are Necessary To Induce A Calcium-dependent...mentioning
confidence: 99%